I assume the equation is supposed to be
![3^{x+2}=8^{x-1}](https://tex.z-dn.net/?f=3%5E%7Bx%2B2%7D%3D8%5E%7Bx-1%7D)
Then we can write
![9\cdot3^x=\dfrac18\cdot8^x\implies\left(\dfrac38\right)^x=\dfrac1{72}](https://tex.z-dn.net/?f=9%5Ccdot3%5Ex%3D%5Cdfrac18%5Ccdot8%5Ex%5Cimplies%5Cleft%28%5Cdfrac38%5Cright%29%5Ex%3D%5Cdfrac1%7B72%7D)
Take the logarithm of base 3/8 on both sides:
![\log_{3/8}\left(\dfrac38\right)^x=\log_{3/8}\dfrac1{72}](https://tex.z-dn.net/?f=%5Clog_%7B3%2F8%7D%5Cleft%28%5Cdfrac38%5Cright%29%5Ex%3D%5Clog_%7B3%2F8%7D%5Cdfrac1%7B72%7D)
![\implies x\log_{3/8}\dfrac38=-\log_{3/8}72](https://tex.z-dn.net/?f=%5Cimplies%20x%5Clog_%7B3%2F8%7D%5Cdfrac38%3D-%5Clog_%7B3%2F8%7D72)
![\implies x=-\log_{3/8}72](https://tex.z-dn.net/?f=%5Cimplies%20x%3D-%5Clog_%7B3%2F8%7D72)
- - -
If the equation is actually
, I'm afraid it cannot be solved exactly.
Answer:
y = 75 - x
Step-by-step explanation:
From the question, we are given variables, and then we can see that
when x = 75 then y = 0
when x = 30 then y = 45
Finding the difference, we have
slope(m) = (45 - 0) / (30 - 75)
slope(m) = 45 / -45
slope(m) = -1
Next, we use the calculated m, to find b, using the formula
y = mx + b
0 = -1 * 75 + b
0 = -75 + b
b = 75
And finally, to get the needed equation, we say that
so y = mX+c
So that
y = -1 * x + 75
y = -x + 75
or y = 75 - x
Answer:
It's kinda hard to see can you type out the question?
Step-by-step explanation:
Answer:
11.6 miles
Step-by-step explanation:
Given that:
Distance from J2 to J3 = 8.7 miles
Distance between J1 and J2 = 1/3 of J2 toJ3
Hence, distance between J1 and J2 becomes :
1/3 * 8.7 miles = 2.9 miles
Distance from J1 to J3 equals :
(J1 to J2) + (J2 to J3)
2.9 miles + 8.7 miles
= 11.6 miles
C. octagon but even though u dont have no picture